Effects of cooling rates on the quality of Prochilodus lineatus (Valenciennes, 1836) sperm - de Jesus Paula, Daniella Aparecida; Murgas, Luis David Solis; Castro, Tássia Flávia Dias; de Lima Assis, Isadora; Neto, Rafael Vilhena Reis [UNESP]; Marcussi, Silvana (Wiley, 2019)
This study aims to investigate the effect of different cooling rates on the semen cryopreservation of curimba (Prochilodus lineatus). Nineteen ejaculates were obtained from adults males and cryopreserved at 15°C/min (CR15), 30°C/min (CR30) (controlled temperature inside and outside straw, speed was stable during freezing) and direct freezing in liquid nitrogen vapour (~35.6°C/min) (CRNV). The straws were thawed and seminal parameters evaluated. DNA fragmentation through the comet assay was assessed. A fresh sperm sample was not frozen and used for analyses. Data were submitted to an analysis of variance (ANOVA), and means were compared by Scott–Knott test (p < 0.05) using the R Software. Mean motility percentage was 100%, and motility duration was 39.5 ± 5.7 s for the fresh sperm (subjective analysis); 58.9 ± 8.0% and 24.5 ± 5.7 s for CR15; 64.8 ± 4.8% and 26.5 ± 7.1 s for CR30; and 50.1 ± 16% and 25.7 ± 4.7 s for CRNV, respectively. Motility percentages were higher and equal between CR15 and CR30 compared to CRNV (p < 0.05). Some sperm motion kinetics, namely average path velocity (VAP) and straight line velocity (VAS), were higher for CR30 (p < 0.05), while curvilinear velocity (VCL) and velocity progression (PRO) were lower for CRNV (p < 0.05). Straightness (STR) and wobble (WOB) were the same among treatments (p > 0.05). Sperm morphology results indicated higher means for total morphological sperm alterations in CRNV. All cooling rates caused sperm DNA fragmentation, although CR30 provided a less harmful effect. This is the first report for cryopreserved P. lineatus sperm preserved under different controlled cooling rates. The cooling rate of 30°C/min is indicated for the cryopreservation of this fish sperm as it led to the lowest detrimental spermatozoa effects.
Keywords: cryopreservation; freezing rate; neotropical fish; reproduction